The Effect of Educational Games on Tooth Brushing Skills in Preschool Children - Zulfan, Meidina Utari; Heriyanto, Yonan; Ningrum, Nining; Nurnaningsih, Hera (Journal Center of Excellent : Health Assistive Technology, 2024)
Educational regarding proper tooth brushing procedures needs to be carried out since preschool, because this is a golden time to build a habit. However, the proportion of correct brushing behavior based on RISKESDAS 2019 is only 2.8%. To overcome this behavior, it is necessary to provide treatment that attracts children's attention, such as providing educational games. The educational game that designed by researchers is about Tooth brushing Simulation using the Doctor Toys Set Educational Game Tool and video for how to play. The purpose of this study was to determine the effect of educational games to improve toothbrushing skills in Atikan Kindergarten, Bandung City. This research method uses a pre-experimental one group pre-test – post-test design which was carried out in April 2022 with a total sampling of 20 children. Toothbrushing skills were observed 2 times, before treatment (pre-test) and after treatment with educational games (post-test). Data analysis used paired-T test. The average score of the correct brushing movement before and after doing the Educational Game on Simulation of Brushing Teeth was 6.65 and 11.85 and there was a significant difference based on the mean score (p<0.05). The conclusion is that an Educational Game about Simulation of Brushing Teeth with Doctor Toys Set and a video of how to play the tool can be used to improve tooth brushing skills in pre-school children.